2014
DOI: 10.1152/ajpregu.00259.2014
|View full text |Cite
|
Sign up to set email alerts
|

Reflex control of inflammation by the splanchnic anti-inflammatory pathway is sustained and independent of anesthesia

Abstract: Following an immune challenge, there is two-way communication between the nervous and immune systems. It is proposed that a neural reflex--the inflammatory reflex--regulates the plasma levels of the key proinflammatory cytokine TNF-α, and that its efferent pathway is in the splanchnic sympathetic nerves. The evidence for this reflex is based on experiments on anesthetized animals, but anesthesia itself suppresses inflammation, confounding interpretation. Here, we show that previous section of the splanchnic ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
0
5

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 38 publications
4
55
0
5
Order By: Relevance
“…For this purpose, we used M1KO and heterozygous AChE+/− mice, since homozygous acetylcholinesterase knockout mice do not develop normally under standard conditions [26]. The spleen was chosen because, as mentioned, it does not have cholinergic innervation [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this purpose, we used M1KO and heterozygous AChE+/− mice, since homozygous acetylcholinesterase knockout mice do not develop normally under standard conditions [26]. The spleen was chosen because, as mentioned, it does not have cholinergic innervation [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…However, the spleen, a major secondary immune organ, seems to be an exception, since no parasympathetic innervation has been detected in this organ. In fact, no connection between cholinergic vagal fibers with retrograde labeled fibers from the spleen could be detected either in the suprarenal ganglia, the left coeliac ganglion or the superior mesenteric ganglia [3][4][5]. Conversely, the sympathetic innervation of the spleen is clearly established.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Recent studies have suggested that the autonomic nervous system, as a regulator of homeostatic processes, modulates peripheral macrophage activation through the activity of the splenic nerve (Martelli et al, 2014). Specifically, nerve terminals in the white pulp of the spleen discharge norepinephrine to activate ␤-adrenergic receptors of nearby T cells.…”
mentioning
confidence: 99%
“…Recent evidence suggests that nAChR␣7 activation in the thalamic reticular nucleus increases both spindle oscillation and the duration of non-REM sleep (Ni et al, 2016). This is particularly interesting given indications that short-term sleep deprivation and the associated increase in slow-wave sleep (SWS) exhibit neuroprotective effects after TBI (Martinez-Vargas et al, 2012). Morawska et al (2016) found that, after TBI, both sleep-restricted rats and rats in which sleep was induced pharmacologically showed average increases in SWS compared with untreated controls.…”
mentioning
confidence: 99%